Amorphous silica nanoparticles caused lung injury through the induction of epithelial apoptosis via ROS/Ca2+/DRP1-mediated mitochondrial fission signaling. Issue 6 (14th September 2022) - Li, Yan; Zhu, Yawen; Zhao, Bosen; Yao, Qing; Xu, Hailin; Lv, Songqing; Wang, Ji; Sun, Zhiwei; Li, Yanbo; Guo, Caixia
Abstract: The adverse effects of amorphous silica nanoparticles (SiNPs) exposure on the respiratory system were increasingly recognized, however, its potential pathogenesis still remains not fully elucidated. So, this study aimed to explore its effects on pulmonary injury, and to investigate related mechanisms. Histological investigations illustrated SiNPs triggered the lung injury, mainly manifested as alveolar structure destruction, collagen deposition, and mitochondrial ultrastructural injury. In particular, SiNPs greatly enhanced pulmonary ROS and TUNEL positive rate in lungs, both of which were positively correlated with lung impairments. Further, the underlying mechanisms were investigated in cultured human bronchial epithelial cells (16HBE). Consistent with the in vivo findings, SiNPs caused the impairments on mitochondrial structure, as well as the activation of ROS generation and oxidative injury. Upon SiNPs stimuli, mitochondrial respiration was greatly inhibited, while Ca 2+ overload in cytosol and mitochondria owing to ER calcium release was noticed, resulting in mitochondrial-dependent epithelial apoptosis. More importantly, mitochondrial dynamics was imbalanced toward a fission type, as evidenced by upregulated DRP1 and its phosphorylation at Ser616 (DRP1 s616 ), while downregulated DRP1 s637, and also MFN1, MFN2. Mechanistic investigations revealed that the activation of ROS/Ca 2+ signaling promoted DRP1-mediated mitochondrial fission by SiNPs, forming a vicious cycle, and ultimately contributing to apoptosis in 16HBE. In summary, our results disclosed SiNPs caused pulmonary injury through the induction of epithelial apoptosis via a ROS/Ca 2+ /DRP1-mediated mitochondrial fission axis.